Needs Analysis of Web-Based Performance Asessment of Network Administration Learning to Improve HOTS Competence. Issue 1 (February 2021) - Ambiyar,; Efendi, Raimon; Waskito,; Afifa, Nur Zamalia; Wulandari, Ratih Agustin
Abstract: This study aims to describe the results of the needs analysis in the process of developing performance appraisal models in learning network administration in the faculty of computer science. This research is a qualitative descriptive study using survey methods to identify the needs of students and teachers in learning assessment. In this study, the analysis of needs is related to the achievement of student learning outcomes and increased ability of High Order Thinking Skills (HOTS), problems faced by students and the media needed by students in the learning assessment process. This study uses a questionnaire given to students who take the Network Administration course #. The results showed that: 1) the lack of learning assessment media that could be used as independent assessments for students; 2) interactive web-based assessment media needed on network administration subjects; 3) high expectations for improving HOTS competence by developing performance appraisal models. Based on these findings, it can be concluded that students and teachers need the development of a performance appraisal model that is interactive appraisal media that can be used as an independent appraisal medium and can improve students HOTS competencies. In addition, these findings will be used in designing performance assessments for courses that have the same characteristics in the Faculty of Computer Science.